5-HT2a receptor antagonism reduces burn-induced macromolecular efflux in rats - Hernekamp, Jochen-Frederick; Klein, H.; Schmidt, Karsten; Kneser, Ulrich; Kremer, Thomas (European journal of trauma and emergency surgery, 2015)
Major thermal injuries lead to a systemic inflammatory response with systemic capillary leakage and multiple organ dysfunction. This systemic inflammatory response is induced by a variety of immunmodulative molecules including TNFα and serotonin. Unspecific serotonin antagonism leads to reduced macromolecular efflux in rat mesenteries after burn plasma transfer. The aim of the present study was to evaluate the effect of specific 5-HT2a antagonism on early burn edema.
Im Ttitel ist die Zahl "2" tiefgestellt
Gesehen am 26.08.2020